Digital Talent Management: A Company Strategy for Facing Technological Disruption - Deri Apriadi; Galuh Boga Kuswara (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The rapid development of digital technology has created disruption in various industrial sectors, requiring companies to adapt through digital-based human resource management. This study aims to analyze the role and strategies of Digital Talent Management in helping companies face the challenges of technological disruption. The research method used was qualitative with a descriptive approach, through literature review and secondary data analysis from various sources related to digital talent management and organizational transformation. The results show that the effective implementation of Digital Talent Management (DTM) can help companies face technological disruption through more adaptive, innovative, and data-driven human resource management. The use of technologies such as AI, people analytics, and HR Tech platforms has been proven to improve recruitment efficiency, competency development, and employee retention. Furthermore, a work culture that supports innovation, continuous learning, and flexible work systems such as remote working also strengthens employee engagement and productivity. With holistic talent management and a positive employee experience, companies can create a competent and highly competitive digital workforce, enabling them to adapt to change and maintain excellence in the era of digital transformation.